Chicken white egg chemerin as a tool for genetic selection for egg weight and hen fertility - Bernardi, Ophélie; Reverchon, Maxime; Estienne, Anthony; Baumard, Yannick; Ramé, Christelle; Brossaud, Adeline; Combarnous, Yves; Froment, Pascal; Dupont, Joëlle (Frontiers in Physiology, 2022)
Embryo mortality rate, which can reach up to 40 % in avian species, is a major issue for breeding. It is therefore important to identify new embryo development biomarkers for genetic selection to improve reproductive performances. We have recently shown that chemerin is expressed in the oviductal hen magnum, accumulates in egg white, is correlated with embryo survival and could thus be used as a molecular marker of embryo development. Eggs from seven hen breeds (n=70) were collected during five successive days at the end of the laying period. After weighing eggs, yolk and albumen, an egg white sample from each egg was collected and a blood sample was taken from each hen. Chemerin concentrations in albumen and blood samples were measured by a specific home made ELISA assay. Hen’s plasma and egg’s albumen chemerin levels were found to be correlated with reproductive parameters such as fecundity, fertility, embryo mortality, hatchability and laying rates. The inter-hen chemerin level variability in albumen was higher than intra-hen except for one breed (R+). We observed significantly different levels of chemerin in egg white between breeds. However, chemerin concentrations in egg white were not significantly associated to variations of hen plasma chemerin levels. Interestingly, we observed negative correlations between albumen chemerin concentrations and egg weight (r=-0.43, p=0.001), between albumen weight (r=-0.40, p=0.002), and between yolk weight (r=-0.28, p=0.03). We also showed negative correlations between egg white chemerin concentrations and fecundity (r=-0.32, p=0.011) and fertility (r=-0.27, p=0.04) whereas no significant correlation was observed with the laying rate. Taken together, these results suggest that egg white chemerin concentration might be a good biomarker for genetic selection for egg weight and fertility in hens, provided these data are confirmed on a larger scale.